2023
DOI: 10.1038/s41598-023-27931-7
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting impacts of dry versus humid heat on US corn and soybean yields

Abstract: The impact of extreme heat on crop yields is an increasingly pressing issue given anthropogenic climate warming. However, some of the physical mechanisms involved in these impacts remain unclear, impeding adaptation-relevant insight and reliable projections of future climate impacts on crops. Here, using a multiple regression model based on observational data, we show that while extreme dry heat steeply reduced U.S. corn and soy yields, humid heat extremes had insignificant impacts and even boosted yields in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…While Tdry tends to peak during the pre-monsoon season throughout the region (van Oldenborgh et al, 2018), recent work has suggested that the highest humid heat magnitudes often occur after monsoon onset in parts of South Asia (Raymond et al, 2020;Rogers et al, 2021). Differentiating between dry and humid heat extremes in this region is particularly important given their distinct impacts on plant and human health, respectively, which can both be detrimental to agricultural production (Diaz et al, 2023;Ting et al, 2023). Ivanovich et al (2022) highlighted that elevated Tw during the June-August season in India is associated with surface level easterly wind anomalies and increased dry bulb temperature and specific humidity, conditions sometimes associated with monsoon breaks.…”
Section: Introductionmentioning
confidence: 99%
“…While Tdry tends to peak during the pre-monsoon season throughout the region (van Oldenborgh et al, 2018), recent work has suggested that the highest humid heat magnitudes often occur after monsoon onset in parts of South Asia (Raymond et al, 2020;Rogers et al, 2021). Differentiating between dry and humid heat extremes in this region is particularly important given their distinct impacts on plant and human health, respectively, which can both be detrimental to agricultural production (Diaz et al, 2023;Ting et al, 2023). Ivanovich et al (2022) highlighted that elevated Tw during the June-August season in India is associated with surface level easterly wind anomalies and increased dry bulb temperature and specific humidity, conditions sometimes associated with monsoon breaks.…”
Section: Introductionmentioning
confidence: 99%